Surgery sterility. Modern trends in tubal surgery. - Ludmir Grimberg, Abraham (2015)
Fine atraumatic instruments should be used, and a number of changes to be used as guides or as dilators (0.4 to 1 mm.) As separators or to approximate structures. It has special clamps, such as Babcock and Williams.